The Effect of Baby Massage on Language Development Disorder (Speech Delay) - Marta Pastari; Syokumawena Syokumawena (Budapest International Research and Critics University, 2022)
This research is directed to answer the following problems; Is there an Influence of Baby Massage on Language Development Disorders (Speech Delay). This study uses a pre-experimental design, because there are variables outside the independent variables that can affect the dependent variable. The research design used was Two Group Pre-Posttest Design (Nuryadi, et al, 2017). The treatment given is; 1) Group I = given Speech Therapy without Oromotor (Speech Therapy Massage) = 16 people; 2) Group II = given Speech Therapy with Oromotor (Speech Therapy Massage) = 16 people. Therapy was given for 3 consecutive months. This research activity was carried out in two places, namely NU_Kids Integrated Therapy 1 and 2. The results of the analysis showed that; 1) Most of the children who were given treatment only with speech therapy (Group I) had severe autism, namely 11 people (68.8%) then most of the children who were given a combination treatment, namely Speech Therapy and Oromotor (Speech Therapy Massage) ) (Group II) also experienced severe autism, namely 9 people (56.3%). This shows that children with severe autism really need speech therapy to deal with communication disorders that can be detected through speech delays (Speech Delay); 2) The results of the different language development test using the Wilcoxon Signed Ranks Test (asymp sig 2-Tailed) showed that in Group I; only children with severe autism category have differences in language development in pre and post treatment; Then in Group II; children with moderate and severe autism categories have differences in language development in pre and post treatment; 3) The ANOVA test results obtained that the F table value from the calculation is 4.17, which is, the calculated F value is in the rejection area (F arithmetic > F table), then H0 is rejected and H1 is accepted. The conclusion is that the speaking ability of the two groups is significantly different, so that it is found that there is